Evaluating the Impact of Covid-19 Lockdown on Business Continuity and Entrepreneurial Resilience in Nigerian Educational Institutions: A Swot Analysis - Lawal, Azeez Tunbosun (Acta Universitatis Danubius. Œconomica, 2024)
During the outbreak of the COVID-19 pandemic, schools across Nigeria were shut down indefinitely, leaving many private school owners struggling to generate income and meet both personal and business-related expenses. Despite this widespread disruption, some private schools were able to continue fulfilling their commitments to key stakeholders. This study aimed to identify the strategies adopted by these schools to navigate the challenges posed by the lockdown. A phenomenological research approach was used to explore the SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis of selected private schools that managed to remain operational, using focus groups to gather data.The results of the study indicated that factors such as digital literacy, teacher motivation, and the size of the school played crucial roles in helping these schools remain functional during the lockdown period. Based on these findings, the study recommends that private school owners should prioritize investments in information and communication technology (ICT) to support both academic and financial operations. Additionally, schools should focus on hiring ICT-savvy and motivated employees. It is also suggested that the government consider providing financial support to the sector, such as recapitalization initiatives, stimulus packages, or concessional loans, to help ensure the long-term viability and growth of private schools.